A theory of firm decline - Fabio Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper carries out an investigation into the socio-economic determinants of couples' childbearing decisions in Italy. Since having children is in most cases a 'couple matter', the analysis accounts for the characteristics of both the possible parents. Our results do not support established theoretical predictions according to which the increase in the opportunity cost of motherhood connected to higher female labour participation is responsible for the fall in fertility. On the contrary, the instability of the women's work status (i.e. their being occasional, precarious, and low-paid workers) reveals to be a significant dissuasive deterrent discouraging the decision to have children. Couples with unemployed women are less likely to plan childbearing as well. Other relevant explanatory variables are current family size and the strength of family ties.
Keywords: C25; J13; Z1; 330; Fertility; Family Planning; Parenthood; Childbearing; Participation; Job Instability; Labour Precariousness; Social Capital; Italy